PREVALENSI HIPOKALEMIA PADA PASIEN DENGAN KEGAWATAN NEUROLOGI DI RUANG RAWAT NEUROLOGI RSUPN CIPTO MANGUNKUSUMO - Aninditha T*, Sitorus F*, Ranakusuma TAS* (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND HYPOKALEMIA IS THE MOST COMMON ELECTROLYTE DISORDERS IN HOSPITALIZED PATIENTS BUT THE PREVALENCE STUDY OF HYPOKALEMIA IN NEUROLOGIC HOSPITALIZED PATIENTS IS REPORTED RARELY